Indigenous knowledge development in Bangladesh : present and future - Sillitoe, Paul, 1949- (Dhaka : University Press, 2000)
Contributed articles.
Includes bibliographical references (p. [219]-238) and index.
ARC
Keywords: Indigenous peoples -- Bangladesh; Indigenous peoples -- Bangladesh -- Politics and government; Bangladesh -- Race relations